2023
DOI: 10.1038/s41598-023-29724-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of PD-L1 and TIGIT expression in non-small cell lung cancer following concurrent chemo-radiotherapy

Abstract: We investigated the effect of preoperative therapy for non-small cell lung cancer on programmed death-ligand 1 (PD-L1), programmed death-1 (PD-1), poliovirus receptor (CD155), and T cell immunoglobulin and immunoreceptor tyrosine-based inhibitory motif (ITIM) domain (TIGIT) expression and prognosis with the cases of 28 patients received preoperative concurrent chemo-radiotherapy (cCRT) and 27 received preoperative drug therapy. The post-treatment PD-L1 expression was higher in cCRT group than in the drug thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… 22 , 23 For example, PD-L1 expression can vary according to anatomical sites and the immunohistochemistry assays used to determine expression. 22 Moreover, RT can induce up-regulation of tumoral PD-L1 expression, 24 , 25 which is relevant in the context of the PACIFIC regimen as tumoral PD-L1 expression is typically determined from tumor samples obtained before receiving CRT. The label approved for durvalumab by the EMA excludes patients with PD-L1 expression on <1% of TCs based on a post hoc analysis, 7 , 12 while similar restrictions are not applied by other regulatory bodies, including the United States FDA.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 For example, PD-L1 expression can vary according to anatomical sites and the immunohistochemistry assays used to determine expression. 22 Moreover, RT can induce up-regulation of tumoral PD-L1 expression, 24 , 25 which is relevant in the context of the PACIFIC regimen as tumoral PD-L1 expression is typically determined from tumor samples obtained before receiving CRT. The label approved for durvalumab by the EMA excludes patients with PD-L1 expression on <1% of TCs based on a post hoc analysis, 7 , 12 while similar restrictions are not applied by other regulatory bodies, including the United States FDA.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that p-stage I adenocarcinoma expressing both CD155 and PD-L1 has a significantly poorer prognosis 15 . Moreover, NSCLC expressing both PD-L1 and TIGIT (ligand for CD155) has a poorer prognosis after neoadjuvant chemoradiotherapy 14 . Sun et al 23 reported that CD155 expression is an independent poor prognostic factor in 334 lung adenocarcinomas (including 137 p-stages II–IV).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells suppress T-lymphocyte activity by expressing TIGIT ligands, such as CD155, also known as poliovirus receptor (PVR) 11 . Accordingly, blockade of the TIGIT/CD155 axis has also emerged as a novel therapeutic strategy for various malignant tumours, including lung cancer 12 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that PD-L1 is a biomarker indicating a poor prognosis and a low survival rate in patients with advanced NSCLC ( 48 - 50 ). When discussing the influence of clinicopathological data on PD-L1 expression, we were surprised to find that T and M staging, especially the T stage, were significantly negatively correlated with PD-L1 levels.…”
Section: Discussionmentioning
confidence: 99%